2022
DOI: 10.3390/children9081191
|View full text |Cite
|
Sign up to set email alerts
|

Parental Knowledge of Appendicitis and Preference for Operative or Non-Operative Treatment at a United Kingdom Children’s Hospital

Abstract: Appendicitis is a common cause of abdominal pain in children, and is the most common reason for children to undergo emergency abdominal surgery. To guide our research program in this field, we aimed to determine parental understanding with regard to appendicitis and its treatment. We also wished to assess parental preference for non-operative or surgical treatment of children with uncomplicated appendicitis. We asked parents attending a children’s outpatient clinic to complete a brief questionnaire that was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…In this study, almost half of the participants recognized the correct anatomical location of the appendix (48%). These findings were superior to those of a survey conducted in the UK, which revealed that one-third of respondents did not know where the appendix was [ 7 ]. The subsequent research found gaps in parental awareness, such as not knowing what appendicitis is (40% of respondents) and underestimating the incidence of appendicitis, which supports our findings.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…In this study, almost half of the participants recognized the correct anatomical location of the appendix (48%). These findings were superior to those of a survey conducted in the UK, which revealed that one-third of respondents did not know where the appendix was [ 7 ]. The subsequent research found gaps in parental awareness, such as not knowing what appendicitis is (40% of respondents) and underestimating the incidence of appendicitis, which supports our findings.…”
Section: Discussioncontrasting
confidence: 96%
“…Regarding the treatment of appendicitis, we found that most of the study population was aware of the current treatment for appendicitis, surgery. These results go in line with another study in the UK [ 7 ]. In this study, only 27.2% of participants thought that it is very likely for the appendix to perforate if the child does not have surgery immediately.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations